Love and Growth: On One Aspect of James Baldwin's Significance for Education. Issue 9 (September 2015) - Frank, Jeff
Background/Context: Although James Baldwin's work is beginning to receive attention by political and social theorists, his work does not currently influence educational conversations. I believe this is unfortunate, and the goal of this article is to make the case that Baldwin's work has a great deal to teach educators, especially teacher educators. Research Design: Reading through all of Baldwin's nonfiction, I draw out interconnected themes that run across his work, and which I found most interesting as I thought about my work as a teacher educator. These themes are: innocence, fear, and love. For each theme, I draw on different aspects of Baldwin's published nonfiction, attempting to create a conversation between aspects of Baldwin's work and issues of importance to teacher educators. Conclusions/Recommendations: I conclude by making the case that Baldwin's work deserves a wider hearing, especially his thinking on love. I develop the concept of "tenacious understanding" to highlight the types of teaching that teacher educators will need to engage in if they are to realize Baldwin's prophetic call that I resound in this article.